Language awareness in teaching - Chadwick, Timothy (Cambridge Univ. Press, 2012)
Includes index; This collection presents new investigations into the role of heritage languages and the correlation between culture and language from a pedagogic and cosmopolitical point of view. Produced with University of Cambridge International Examinations, the Toolkit helps teachers to develop language awareness to support their students with the academic language they need to be successful in subjects taught through English. With reflective questions and activities, it can be used either for self-study or in training modules. Useful for both content and English language teachers, it is aimed primarily at those who teach students for whom English is not their first language - for example as part of a bilingual or CLIL programme or in an international English-medium school